Lightweight board, its manufacturing method and structural material

The lightweight panel, made by impregnating glass cloth with thermosetting resin and bonding it to polycarbonate foam, addresses the issues of lateral rigidity and adhesion in conventional materials, providing high rigidity, toughness, and ease of processing.

JP7602896B2Active Publication Date: 2024-12-19JSP CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020191814
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-18
Publication Date
2024-12-19
Estimated Expiration
2040-11-18

AI Technical Summary

Technical Problem

Conventional sandwich structural materials lack lateral rigidity, have limited adhesive strength due to small adhesion areas with surface decorative boards, and are difficult to process due to large voids in the core material, while reinforcing materials for outer panels do not provide sufficient strength and adhesion with polycarbonate resin details.

Method used

A lightweight panel is created by impregnating glass cloth with a thermosetting resin and applying it to both sides of a polycarbonate foam with a 5 to 20 times expansion ratio, using a 100% solid content adhesive, and forming a surface layer material with a thickness of 0.2 to 2.0 mm, which is then bonded to decorative boards using a urethane or epoxy resin.

Benefits of technology

The solution results in a lightweight board with high surface rigidity, excellent toughness, and ease of post-processing, suitable for forming structural materials with arbitrary shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602896000005
    Figure 0007602896000005
  • Figure 0007602896000006
    Figure 0007602896000006
  • Figure 0007602896000001
    Figure 0007602896000001
Patent Text Reader

Abstract

To provide a lightweight board having a high surface rigidity and excellent toughness, a manufacturing method thereof, and a structural material.SOLUTION: There is provided a lightweight board that is obtained by: impregnating a thermosetting resin into a glass cloth; and laminating a surface layer material 12 performed of a hot-press molding and has a thickness of 0.2 mm or more and 2.0 mm or less onto the front and back sides of a plastic foam body (foam body 11) with a foam ratio of 5 times or more and 20 times or less by using an adhesive having 100% solid content, in which the plastic foam body is a polycarbonate resin. A basis weight of the glass cloth may be in a range of 50 g / m2 or more and 200 g / m2 or less. The thermosetting resin may be one kind of resin selected from an epoxy-based resin, phenol-based resin, a polyester-based resin, a diallyl-phthalate-based resin, or a mixture of two or more kinds thereof. The number of laminated glass cloths may be one or more. The adhesive having 100% solid content may be an urethane-based resin or an epoxy-based resin.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lightweight board having high surface rigidity and excellent toughness, a manufacturing method thereof, and a structural material thereof. [Background technology]

[0002] There is a demand for lightweight, high-strength materials in various fields, and measures have been taken to meet this demand. In the field of building materials, flash and honeycomb structures are used as core materials to reduce the weight of building fixtures.

[0003] Furthermore, a "reinforcement material for exterior panels" has been known in the art, which is formed by laminating a reinforcing layer made of a resin-impregnated glass cloth to a resin layer (see paragraphs

[0059] to

[0062] and Figs. 1 and 2 of Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2011-148091 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, while conventional sandwich structural materials are lightweight and have high rigidity in the vertical direction (surface direction), they have low rigidity in the lateral directions. Furthermore, since the cross section of the flush and honeycomb structures is linear in both the face and side directions, the bonding area with the surface decorative plate is extremely small, making it difficult to obtain sufficient adhesive strength. Furthermore, after processing into a sandwich structure material, cutting is difficult due to the large voids in the core material.

[0006] A plastic foam can also be used as the core material. The foam core is uniformly configured regardless of location, so there is a sufficient bonding area with the surface decorative plate. However, if the strength of the foam core is weak, there is a high possibility that the foam will break when a large force is applied.

[0007] On the other hand, the conventional "outer panel reinforcing material" (Patent Document 1) is attached to the outer panels of various industrial machines such as transport machines to reinforce the outer panels, and has a different use from that of the present invention. In addition, there is no mention of "polycarbonate-based resin" in the resin layer, nor is there any mention of the basis weight of the glass cloth.

[0008] The present invention has been made in consideration of the problems of the conventional technology, and has an object to provide a "lightweight panel" that is light-weight and has high toughness and is easy to process afterwards. It is also an object to provide a "structural material" obtained by processing the lightweight panel. [Means for solving the problem]

[0009] The "lightweight panel" according to one embodiment of the present invention is characterized in that a surface material having a thickness of 0.2 mm to 2.0 mm, which is made by impregnating glass cloth with a thermosetting resin and hot-press molding it, is attached to the front and back of a plastic foam having an expansion ratio of 5 to 20 times using an adhesive with a 100% solid content, and the plastic foam is made of a polycarbonate-based resin. In addition, in the "lightweight panel" according to one embodiment of the present invention, the basis weight of the glass cloth is 50 g / m 2 More than 200g / m 2 It is characterized by the following range:

[0010] The "lightweight panel" according to one embodiment of the present invention is characterized in that the thermosetting resin is one type of resin selected from the group consisting of epoxy resin, phenolic resin, polyester resin, and diallylphthalate resin, or a mixture of two or more types. The "lightweight panel" according to one aspect of the present invention is characterized in that the number of laminated glass cloth sheets is two or more.

[0011] The "lightweight panel" according to one aspect of the present invention is characterized in that the adhesive having a solid content of 100% is a urethane-based resin or an epoxy-based resin. The "lightweight panel" according to one aspect of the present invention is characterized in that the surface layer is formed by bonding a plurality of decorative panels, which are hot-press molded on a laminate of the glass cloth and printed paper impregnated with the thermosetting resin, to each other using the adhesive with a solid content of 100%.

[0012] One embodiment of the "method of manufacturing a lightweight panel" of the present invention is characterized in that a foam is prepared by foaming a polycarbonate-based resin at an expansion ratio of 5 to 20 times, a thermosetting resin is impregnated into glass cloth, and a surface material having a thickness of 0.2 to 2.0 mm is formed by hot press molding, an adhesive having a solid content of 100% is applied to one of the front and back sides of the plastic foam, the surface material is bonded, the adhesive is applied to the other front and back side of the plastic foam, the surface material is bonded, and the material is dried under pressure for a predetermined period of time. The "structural material" according to one embodiment of the present invention is characterized in that the lightweight board is cut into any shape and the cut lightweight boards are joined together with the adhesive to form the desired shape.

[0013] One embodiment of the "structural material" of the present invention is characterized in that a plastic foam is prepared by foaming a polycarbonate resin at an expansion ratio of 5 to 20 times, a glass cloth is impregnated with a thermosetting resin, and a surface material having a thickness of 0.2 to 2.0 mm is formed by hot pressing the plastic cloth, an adhesive having a solid content of 100% is applied to one of the front and back sides of the plastic foam, the surface material is bonded, the adhesive is applied to the other of the front and back sides of the plastic foam, the surface material and the plastic foam are bonded alternately to create a structure, the adhesive is applied to one of both end faces of the structure, the surface material is bonded, and the surface material is bonded to the other of both end faces of the structure, so that all four sides are surrounded by the surface material. Effect of the Invention

[0014] According to one aspect of the present invention, it is possible to provide a lightweight board having high surface rigidity and excellent toughness, a manufacturing method thereof, and a structural material thereof. [Brief description of the drawings]

[0015] [Figure 1] 1 is a cross-sectional view of a lightweight board according to a first embodiment. [Diagram 2] FIG. 11 is a cross-sectional view of a structural material according to a third embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] (Lightweight board 10 according to the first embodiment) In FIG. 1, reference numeral 10 denotes a lightweight board according to the first embodiment. The lightweight board is a sandwich structural material having surface layers 12 on both sides of a plastic foam (hereinafter referred to as "foam 11"), and in particular a fiber-reinforced plastic sandwich structural material using glass cloth impregnated with a thermosetting resin, pressurized and heated, as the surface layer 12.

[0017] The foam 11 is extremely lightweight because it is porous, and has excellent soundproofing, vibration-proofing, and heat-insulating properties. The surface layer material 12 is made of glass cloth impregnated with a thermosetting resin, and has strength and rigidity.

[0018] (Foam 11) The foam 11 is a plastic foam and is made of a polycarbonate-based resin. The polycarbonate-based resin means a polycarbonate ester formed from carbonic acid and glycol or bisphenol, etc., and in particular, aromatic polycarbonate-based resins derived from bisphenols such as 2,2-bis(4-oxyphenyl)propane, 2,2-bis(4-oxyphenyl)butane, 1,1-bis(4-oxyphenyl)cyclohexane, 1,1-bis(4-oxyphenyl)butane, 1,1-bis(4-oxyphenyl)isobutane, and 1,1-bis(4-oxyphenyl)ethane are preferably used.

[0019] The polycarbonate resin may contain other resins such as polyethylene resin, polyester resin, acrylic resin, etc., in an amount of less than 50% by weight of the total. The mixing ratio of the other resins is preferably 10% by weight or less, more preferably 5% by weight or less, and further preferably consists of only polycarbonate resin.

[0020] The foam 11 is produced by foaming the polycarbonate resin by extrusion foaming, injection foaming, press foaming, in-mold molding of foamed particles, etc., but it is preferable to use a foam plate obtained by extrusion foaming, since it is easy to obtain a long foam plate and a foam with a high expansion ratio. In addition, the foam plate obtained by extrusion foaming is preferable because, when the surface skin of the foam plate obtained by extrusion foaming is cut and used, the bubbles are exposed on the foam surface, and therefore, when the foam plate is bonded to a surface material using an adhesive, a lightweight board with excellent adhesiveness can be obtained. In addition, when the foam 11 is a foam plate, when one side of the board is the front, the opposite side to the front is the back.

[0021] The expansion ratio of the foam 11 is 5 to 20 times. From the viewpoints of light weight and heat insulation, the lower limit of the expansion ratio is 5 times, preferably 7 times or more, and more preferably 10 times or more. From the viewpoint of rigidity, the upper limit of the expansion ratio is 20 times, preferably 18 times or less, and more preferably 15 times or less. In this specification, the expansion ratio of the foam 11 is calculated by dividing the density of the resin constituting the foam 11 by the apparent density of the foam 11. The apparent density of the foam 11 can be determined in accordance with JIS K 6767 (1999).

[0022] The foam 11 preferably has a thickness of 10 mm or more, more preferably 20 mm or more. The upper limit of the thickness of the extruded foam board is about 120 mm. The thickness of the foam 11 can be determined by dividing the widthwise vertical cross section of the foam 11 from one end to the other end at equal intervals to determine 20 or more measurement points excluding both ends, and then measuring the thickness of the foam 11 at each of the 20 or more measurement points, and calculating the arithmetic mean value of the measured values. The foam 11 preferably has a width of 300 mm or more, more preferably 350 mm or more, and even more preferably 400 mm or more. The upper limit of the width of the foam 11 is about 2000 mm. The foam 11 preferably has a length of 1000 mm or more, more preferably 1500 mm or more, and the upper limit of the length of the foam 11 is about 10000 mm.

[0023] The closed cell ratio of the foam 11 is preferably 70% or more, more preferably 80% or more, and even more preferably 85% or more. The closed cell ratio S (%) is calculated from the true volume Vx of the foam 11 measured using an air comparison type specific gravity meter (e.g., air comparison type specific gravity meter, model: 930, manufactured by Toshiba Beckman Co., Ltd.) according to procedure C of ASTM-D2856-70, using the following formula (1).

[0024] S(%)=(V X -W / ρ)×100 / (V A -W / ρ) (1) Where, Vx is the true volume (cm) of the cut sample obtained by measuring with the air comparison type specific gravity meter mentioned above. 3 ) (corresponding to the sum of the volume of the resin constituting the cut sample of the foam 11 and the total volume of the air bubbles in the closed cell portion in the cut sample.) V A : Apparent volume (cm) of cut sample calculated from the outer dimensions of the cut sample used in the measurement 3 ) W: Total weight of cut sample used for measurement (g) ρ: density of the resin constituting the foam 11 (g / cm 3 )

[0025] The average cell diameter in the thickness direction of the foam 11 is preferably 0.08 mm to 3.0 mm. When the average cell diameter is within this range, the foam can fully exhibit basic physical properties such as compressive strength and heat insulation. From this viewpoint, the average cell diameter in the thickness direction is more preferably 0.2 to 2.5 mm, and further preferably 0.5 to 2.0 mm. The method for measuring the average cell diameter is as follows. T : mm) and the average cell diameter (D W First, a cross section perpendicular to the width direction of the foam 11 (a vertical cross section perpendicular to the extrusion direction of the foam 11) is measured to determine the average cell diameter (D L To determine the average cell diameter in each direction, a magnified microscope photograph is taken of a cross section of the foam 11 perpendicular to the extrusion direction (a vertical cross section parallel to the extrusion direction of the extruded foam plate, dividing it in half at the center in the width direction). A straight line is then drawn on the magnified photograph in the direction to be measured, and the number of bubbles that intersect with the line is counted. The length of the line (obviously, this length does not refer to the length of the line on the magnified photograph, but the true length of the line taking into account the magnification rate of the photograph) is divided by the number of counted bubbles to determine the average cell diameter in each direction. The average cell diameter (D H : mm) is the average cell diameter (D W ) and the average cell diameter in the extrusion direction of foam 11 (D L ) is the arithmetic mean value.

[0026] Furthermore, the foam 11 preferably has a cell deformation ratio of 1.2 to 3.5. The cell deformation ratio is defined as the average cell diameter (D T ) is the average cell diameter (D H ) is divided by the value (D T / D H), and the smaller the cell deformation ratio is than 1, the flatter the cells are, and the larger it is than 1, the longer the cells are. When the cell deformation ratio is within the above range, the foam 11 has excellent mechanical strength and high thermal insulation properties. From the above viewpoints, the cell deformation ratio is more preferably 1.5 to 3.2, and even more preferably 1.8 to 3.0.

[0027] (Surface material 12) The surface layer material 12 is formed by impregnating a glass cloth with a thermosetting resin and subjecting it to hot press molding. The thickness of the surface layer material 12 is preferably, for example, 0.2 mm to 2.0 mm. The lower limit of the thickness is preferably 0.2 mm or more from the viewpoint of toughness and workability, and the upper limit is preferably 2.0 mm or less from the viewpoint of lightweight.

[0028] The basis weight of the glass cloth is, for example, 50 g / m 2 More than 200g / m 2 The following range is preferable. The lower limit of the basis weight is 50 g / m from the viewpoint of maintaining the amount of impregnation of the thermosetting resin. 2 The upper limit is preferably 200 g / m or more from the viewpoint of drying after impregnation with the thermosetting resin. 2 The following is desirable:

[0029] The thermosetting resin is preferably one of epoxy resins, phenol resins, unsaturated polyester resins, and diallylphthalate resins, or a mixture of two or more of these resins, from the viewpoints of impregnation into glass cloth, workability in an impregnation machine, dimensional stability after thermo-compression molding, and strength.

[0030] The number of laminated glass cloths may be one or more. The number of laminated sheets is preferably, for example, 3 to 10. The lower limit is 1 sheet to increase the strength of the foam, and 3 or more sheets are more preferable to make glue ducts less noticeable when laminated, and the upper limit is preferably 10 sheets so that sufficient heat and pressure can be applied when laminated.

[0031] In addition, the number of laminated sheets is based on "glass cloth," but is not limited to this. Glass cloth impregnated with thermosetting resin and heated is called "prepreg," and this "prepreg" may also be used as the basis. Incidentally, the "prepreg" is a semi-finished product produced during the production of the surface layer material 12 or the "decorative board" described below, and corresponds to a sheet-like material or a reinforced plastic molding material.

[0032] In addition, a laminate of multiple "prepregs" and pressing them together in a heat press is called a "decorative board," and this "decorative board" may be used as the basis for the number of laminated sheets. In addition, like "prepreg," the term "decorative board" is used to mean a semi-finished product produced in the middle of manufacturing the surface layer material 12. In contrast, the surface material 12 is used to mean an assembly of "prepregs" or "decorative panels."

[0033] (Method of manufacturing the lightweight board 10) The method for manufacturing the lightweight board 10 involves preparing a foam 11 having a predetermined thickness by foaming a polycarbonate resin at a predetermined ratio (for example, 5 times or more and 20 times or less). The glass cloth used for the surface layer 12 (for example, 50 g / m 2 More than 200g / m 2 The prepreg is impregnated with a predetermined thermosetting resin (e.g., epoxy resin, phenolic resin, polyester resin, diallylphthalate resin) and heated to produce a prepreg. Two or more prepregs are laminated and pressed in a heating press at a certain temperature (e.g., 230°C) for a certain time (e.g., 30 minutes) to heat cure the prepreg, forming a surface layer 12 (or decorative plate) with a predetermined thickness (e.g., 0.2 mm to 2.0 mm).

[0034] Although not shown, a surface material 12 (or a decorative plate) is attached to the front and back of the foam 11 using an adhesive with a solid content of 100%, thereby producing the lightweight board 10. The adhesive with 100% solid content is, for example, a urethane resin or an epoxy resin. The adhesive is applied to one side of the foam 11 using a rubber roller, and the surface material 12 (or decorative plate) is attached. In a similar manner, the surface material 12 (or decorative plate) is attached to the other side of the foam 11, and the board is dried under predetermined conditions (for example, a temperature of 23° C. and a relative humidity of 50%), under a certain pressure (for example, by placing a weight on the board) for a predetermined time (for example, overnight), to obtain the lightweight board 10.

[0035] (Modification of surface layer material 12) A variation of the surface material 12 is characterized in that a glass cloth impregnated with a thermosetting resin and printed paper with a pattern such as wood grain are laminated together, and then multiple sheets of decorative boards that have been hot-press molded are bonded to the foam 11 using an adhesive with a 100% solid content. According to this modification, there is an advantage that a lightweight board with a design can be manufactured in the same process by laminating the glass cloth and the printed paper.

[0036] (Structural materials related to the second implementation committee form) Next, although not shown, a structural material according to a second embodiment will be described. The structural material according to the second embodiment is characterized in that, although not shown, a lightweight board 10 is cut into any desired shape and the cut lightweight boards are joined together with an adhesive to form the desired shape. According to the second embodiment, a structural material 20 having any desired shape can be obtained.

[0037] (Structural material according to the third embodiment) A structural material 20 according to a third embodiment will be described with reference to FIG. The structural material 20 according to the third embodiment is prepared by applying an adhesive with a solid content of 100% to one surface of a foamed body 11 using a rubber roller, and then bonding a surface material 12 (or a decorative plate).

[0038] A surface material 12 (or a decorative plate) was attached to the other surface of the foam 11 in a similar manner. Furthermore, foam 11 coated with adhesive and surface material 12 (or decorative plate) were alternately laminated to produce a structure having six layers of foam 11 with surface material 12 (or decorative plate) sandwiched between them. The term "structure" is used to mean a semi-finished product produced during the manufacturing process of the structural material 20.

[0039] This structure was placed in a press and pressed for 12 hours. Adhesive was applied to the end surface of the structure in the same manner as above, and a surface material 12 (or decorative board) was attached, and a surface material 12 (or decorative board) was also attached to the other side, creating a structure surrounded on four sides by the surface material 12 (or decorative board). This structure was placed in a press and pressed for 12 hours to obtain the structural material 20 according to the third embodiment. According to the third embodiment, it is possible to provide a structural material 20 whose four sides are surrounded by a surface material 12 (or a decorative plate). EXAMPLES

[0040] Examples 1 to 11 of the lightweight board and structural material according to the present invention and Comparative Examples 1 to 9 will be described below. Note that the present invention is not limited to the following Examples 1 to 10.

[0041] Example 1 The configuration of the first embodiment is as shown in Table 1 below. In addition, in Table 1 below, in addition to Example 1, the configurations of Examples 2 to 10 are also shown. [Table 1]

[0042] In Example 1, as shown in Table 1 above, polycarbonate resin (resin density 1.2 g / cm 3 A foam (product name: MiraPolyca (registered trademark) Foam, JSP Corporation) made by expanding polycarbonate resin by 12 times, with a thickness of 50 mm, width of 300 mm, and length of 1800 mm, was prepared. The front and back of the polycarbonate resin foam were cut. Glass cloth used as surface material: 200g / m 2(product name: K7628WT-1270 S640 manufactured by Arisawa Seisakusho) was used, which was impregnated with unsaturated polyester resin (product name: DH2000B manufactured by DIC Corporation) as a thermosetting resin, and heated to prepare a prepreg.

[0043] The two prepregs were pressed and heat-cured in a heat press at 230° C. for 30 minutes to produce a decorative board with a surface layer 12 having a thickness of 0.3 mm. A urethane adhesive (product name: KU550 by Konishi Co., Ltd.) was applied to one side of the foam using a rubber roller, and two layers of decorative board were attached to form a surface material located on one side of the foam. Two layers of decorative board were attached to the other side of the foam in the same manner, forming a surface material located on the other side of the foam. After that, a weight was placed on top and the foam was dried overnight, i.e., 400 kg / m 2 The board was then dried for 8 hours to obtain the lightweight board of Example 1. The weight of the resulting lightweight board is 6.4 kg / m 2 It became.

[0044] Example 2 In Example 2, a foam (product name: MiraPolyca (registered trademark) Foam, JSP Corporation) made by foaming polycarbonate resin 12 times, having a thickness of 50 mm, a width of 300 mm, and a length of 1800 mm was prepared. Glass cloth used as surface material: 200g / m 2 (Product name: K7628WT-1270 S640, manufactured by Arisawa Manufacturing Co., Ltd.) was used, and the prepreg was made by impregnating it with unsaturated polyester resin (Product name: DH2000B, manufactured by DIC Corporation) as a thermosetting resin and heating it. Five prepregs were laminated and pressed together in a heat press at 230°C for 30 minutes to form a decorative board with a surface layer material 12 having a thickness of 0.8 mm.

[0045] A urethane adhesive (product name: KU550, Konishi Co., Ltd.) was applied to one side of the foam using a rubber roller, and five layers of decorative board were attached to form a surface material located on one side of the front and back. In the same manner, five layers of decorative board were attached to the other side of the foam, and a surface material located on the other side of the front and back was formed. After that, a weight was placed on top and the board was dried overnight to obtain the lightweight board of Example 2. The weight of the resulting lightweight board is 9 kg / m 2 It became.

[0046] Example 3 In Example 3, a foam (product name: MiraPolyca (registered trademark) Foam, JSP Corporation) made by foaming polycarbonate resin 12 times, having a thickness of 50 mm, a width of 300 mm, and a length of 1800 mm was prepared. Glass cloth used as surface material: 200g / m 2 (Product name: K7628WT-1270 S640, manufactured by Arisawa Seisakusho) was used, impregnated with unsaturated polyester resin (Product name: DH2000B, manufactured by DIC Corporation) as a thermosetting resin, and heated to produce a prepreg. Ten prepregs were laminated and pressed together in a heat press at 230°C for 30 minutes to produce a decorative board with a surface layer 12 thickness of 1.6 mm.

[0047] A urethane adhesive (product name: KU550, Konishi Co., Ltd.) was applied to one side of the foam with a rubber roller, and 10 layers of decorative board were attached. In the same manner, 10 layers of decorative board were attached to the other side of the foam. A surface material was formed on the other side of the front and back. After that, a weight was placed on it and it was dried overnight to obtain the lightweight board of Example 3. The weight of the resulting lightweight board is 11.2 kg / m 2 It became.

[0048] Example 4 In Example 4, a foam (product name: MiraPolyca (registered trademark) Foam, JSP Corporation) made by foaming polycarbonate resin 12 times, with a thickness of 50 mm, a width of 300 mm, and a length of 1800 mm was prepared. Glass cloth used for the surface layer is 50g / m 2 (product name: 1080NT-1270 S640, manufactured by Arisawa Seisakusho) was used, which was impregnated with unsaturated polyester resin (product name: DH2000B, manufactured by DIC Corporation) as a thermosetting resin, and heated to produce a prepreg. Ten prepregs were laminated and pressed together in a heat press at 230° C. for 30 minutes to produce a decorative board with a surface layer 12 having a thickness of 0.2 mm.

[0049] A urethane adhesive (product name: KU550, Konishi Co., Ltd.) was applied to one side of the foam with a rubber roller, and 10 layers of decorative board were attached. In the same manner, 10 layers of decorative board were attached to the other side of the foam. A surface material was formed on the other side of the front and back. After that, a weight was placed on it and it was dried overnight to obtain the lightweight board of Example 4. The weight of the resulting lightweight board is 7.5 kg / m 2 It became.

[0050] Example 5 In Example 5, a foam (product name: MiraPolyca (registered trademark) Foam, JSP Corporation) made by foaming polycarbonate resin 12 times, having a thickness of 50 mm, a width of 300 mm, and a length of 1800 mm was prepared. Glass cloth used as surface material: 200g / m 2 (Product name: K7628WT-1270 S640, manufactured by Arisawa Seisakusho) was used, impregnated with unsaturated polyester resin (Product name: DH2000B, manufactured by DIC Corporation) as a thermosetting resin, and heated to produce a prepreg. Thirteen prepregs were laminated and pressed together in a heat press at 230°C for 30 minutes to produce a decorative board with a surface layer 12 thickness of 2.0 mm.

[0051] A urethane adhesive (product name: KU550, Konishi Co., Ltd.) was applied to one side of the foam with a rubber roller, and 13 layers of decorative board were attached. In the same manner, 13 layers of decorative board were attached to the other side of the foam. A surface material was formed on the other side of the front and back. After that, a weight was placed on it and it was dried overnight to obtain the lightweight board of Example 5. The weight of the resulting lightweight board is 13.8 kg / m 2 It became.

[0052] Example 6 In Example 6, a foam (product name: MiraPolyca (registered trademark) Foam, JSP Corporation) made by foaming polycarbonate resin five times, having a thickness of 50 mm, a width of 300 mm, and a length of 1800 mm was prepared. Glass cloth used as surface material: 200g / m 2(Product name: K7628WT-1270 S640, manufactured by Arisawa Seisakusho) was used, and the prepreg was made by impregnating it with unsaturated polyester resin (Product name: DH2000B, manufactured by DIC Corporation) as a thermosetting resin and heating it. Two prepregs were laminated and pressed together in a heat press at 230°C for 30 minutes to produce a decorative board with a surface layer material 12 of 0.3 mm in thickness.

[0053] A urethane adhesive (product name: KU550, Konishi Co., Ltd.) was applied to one side of the foam with a rubber roller, and two layers of decorative board were attached. In the same manner, two layers of decorative board were attached to the other side of the foam. A surface material was formed on the other side of the front and back. After that, a weight was placed on it and it was dried overnight to obtain the lightweight board of Example 6. The weight of the resulting lightweight board is 7.8 kg / m 2 It became.

[0054] Example 7 In Example 7, a foam (product name: MiraPolyca (registered trademark) Foam, JSP Corporation) made by foaming polycarbonate resin 20 times, having a thickness of 50 mm, a width of 300 mm, and a length of 1800 mm was prepared. Glass cloth used as surface material: 200g / m 2 (Product name: K7628WT-1270 S640, manufactured by Arisawa Seisakusho) was used, and the prepreg was made by impregnating it with unsaturated polyester resin (Product name: DH2000B, manufactured by DIC Corporation) as a thermosetting resin and heating it. Two prepregs were laminated and pressed together in a heat press at 230°C for 30 minutes to produce a decorative board with a surface layer material 12 of 0.3 mm in thickness.

[0055] A urethane adhesive (product name: KU550, Konishi Co., Ltd.) was applied to one side of the foam with a rubber roller, and two layers of decorative board were attached. In the same manner, two layers of decorative board were attached to the other side of the foam. A surface material was formed on the other side of the front and back. After that, a weight was placed on it and it was dried overnight to obtain the lightweight board of Example 7. The weight of the resulting lightweight board is 6.0 kg / m 2 It became.

[0056] Example 8 In Example 8, a foam (product name: MiraPolyca (registered trademark) Foam, JSP Corporation) made by foaming polycarbonate resin 12 times, having a thickness of 50 mm, a width of 300 mm, and a length of 1800 mm was prepared. Glass cloth used as surface material: 200g / m 2 A prepreg was made by impregnating a thermosetting resin (product name: K7628WT-1270 S640 manufactured by Arisawa Manufacturing Co., Ltd.) with unsaturated polyester resin (product name: DH2000B manufactured by DIC Corporation) as a thermosetting resin and heating it. Five prepregs were laminated and pressed in a heat press at 230°C for 30 minutes. Instead of using a typical flat mirror plate, a sand-grained embossed plate was used to combine them together, resulting in a decorative board with a surface layer 12 thickness of 0.8 mm. The sand-grained unevenness of the embossed plate was transferred to the surface of the decorative board.

[0057] A urethane adhesive (product name: KU550, Konishi Co., Ltd.) was applied to one side of the foam with a rubber roller, and five layers of decorative board were attached. In the same manner, five layers of decorative board were attached to the other side of the foam. A surface material was formed on the other side of the front and back. After that, a weight was placed on it and it was dried overnight to obtain the lightweight board of Example 8. The resulting lightweight board has an anti-slip surface due to the embossed surface. The weight is 6.4 kg / m 2 It became.

[0058] Example 9 In Example 9, a foam (product name: MiraPolyca (registered trademark) Foam, JSP Corporation) made by foaming polycarbonate resin 12 times, having a thickness of 50 mm, a width of 300 mm, and a length of 1800 mm was prepared. Glass cloth used as surface material: 200g / m 2A prepreg was made by impregnating a thermosetting resin (product name: K7628WT-1270 S640, manufactured by Arisawa Manufacturing Co., Ltd.) with unsaturated polyester resin (product name: DH2000B, manufactured by DIC Corporation) as the thermosetting resin and heating it. Five prepregs were laminated and pressed in a heat press at 230°C for 30 minutes, with titanium paper printed with a wood grain pattern on the surface placed on top, and the prepregs were integrated to create a decorative board with a surface material 12 of 0.9 mm thickness. The decorative board was given a wood grain design. Titanium paper is a printed paper with good resin impregnation properties that is also used in melamine decorative boards.

[0059] A urethane adhesive (product name: KU550, Konishi Co., Ltd.) was applied to one side of the foam with a rubber roller, and five layers of decorative board were attached. In the same manner, five layers of decorative board were attached to the other side of the foam. A surface material was formed on the other side of the front and back. After that, a weight was placed on it and it was dried overnight to obtain the lightweight board of Example 9. The resulting lightweight board has a beautiful wood grain design. It weighs 6.6kg / m 2 It became.

[0060] Example 10 In Example 10, a foam (product name: MiraPolyca (registered trademark) Foam, JSP Corporation) made by foaming polycarbonate resin 12 times, having a thickness of 50 mm, a width of 300 mm, and a length of 1800 mm was prepared. Glass cloth used as surface material: 200g / m 2 (Product name: K7628WT-1270 S640, manufactured by Arisawa Seisakusho) was used, impregnated with unsaturated polyester resin (Product name: DH2000B, manufactured by DIC Corporation) as a thermosetting resin, and heated to produce a prepreg. Ten prepregs were laminated and pressed together in a heat press at 230°C for 30 minutes to produce a decorative board with a surface layer 12 thickness of 1.6 mm.

[0061] A urethane adhesive (product name: KU550, Konishi Co., Ltd.) was applied to one side of the foam with a rubber roller, and 10 layers of decorative board were attached. In the same manner, 10 layers of decorative board were attached to the other side of the foam. A surface material was formed on the other side of the front and back. After that, a weight was placed on top and it was dried overnight to obtain the lightweight board of Example 10. The weight of the resulting lightweight board is 11.2 kg / m 2 It became.

[0062] Furthermore, foam coated with adhesive and decorative panels were alternately laminated on top of the foam to create a structure with six layers of foam and decorative panels sandwiched between them. This structural material was placed in a press and pressed for 12 hours. Adhesive was applied to the end surface of the structure in the same manner as above, and 10 layers of decorative boards were attached to the other side, creating a structure surrounded by decorative boards on all four sides, i.e., the surface material. This structure was placed in a press and pressed for 12 hours to obtain a structural material according to Example 10. The weight of the resulting structure is 44.3 kg / m 2 It became.

[0063] Example 11 Example 11 was the same as Example 2 except that the thermosetting resin was a urea resin, and a lightweight board of Example 11 was obtained.

[0064] Comparative Example 1 The configuration of Comparative Example 1 is as shown in Table 2 below. In addition, in Table 1 below, the configurations of Comparative Example 1 as well as Comparative Examples 2 to 8 are also shown. [Table 2]

[0065] Comparative Example 1 was the same as Example 2 except that the foam material was polystyrene as shown in Table 2 above, and a lightweight board of Comparative Example 1 was obtained.

[0066] Comparative Example 2 Comparative Example 2 was the same as Example 2 except that the adhesive used was a chloroprene rubber-based adhesive, and a lightweight board of Comparative Example 2 was obtained.

[0067] Comparative Example 3 Comparative Example 3 was the same as Example 1 except that the number of laminated glass cloths was one and the thickness of the surface layer material 12 was 0.15 mm, and a lightweight board of Comparative Example 3 was obtained.

[0068] Comparative Example 4 Comparative Example 4 was the same as Example 1 except that the number of laminated glass cloths was 15 and the thickness of the surface layer material 12 was 2.4 mm, and a lightweight board of Comparative Example 4 was obtained.

[0069] Comparative Example 5 Comparative Example 5 was the same as Example 1 except that the foaming ratio of the foam was four times that of Example 1, and a lightweight board of Comparative Example 5 was obtained.

[0070] Comparative Example 6 Comparative Example 6 was the same as Example 1 except that the expansion ratio of the foam was 23 times, and a lightweight board of Comparative Example 6 was obtained.

[0071] Comparative Example 7 In Comparative Example 7, the basis weight of the glass cloth is 40 g / m 2 However, when the thermosetting resin was impregnated, the amount of the resin was small, and even when two sheets were laminated and heated and compressed, the adhesive strength between the layers could not be obtained. Therefore, a lightweight board could not be obtained.

[0072] Comparative Example 8 In Comparative Example 8, the basis weight of the glass cloth is 210 g / m 2 However, when the thermosetting resin was impregnated and dried, the amount of the resin was large, and drying was insufficient, so when the prepregs were produced and laminated, the prepregs bonded to each other at room temperature, resulting in a blocking state. As a result, it was not possible to obtain a lightweight board.

[0073] (Evaluation method and criteria) There are 13 types of evaluation methods, i.e., physical property evaluation, for lightweight boards and structural materials: The evaluation criteria for the evaluation methods (1) to (13) will be described later. (1) Bending strength (2) Bending failure state (3) Condition of glue dripping (4) Workability / processability (5) Lightweight (6) Thermal insulation (7) Rigidity (8) Prepreg performance and productivity (9) Observation of condition after bending test (10) Design (11) Machinability (wear of cutting tools) (12) Adhesiveness (13) Overall rating

[0074] (Bending strength) The bending strength was gradually increased, and the value at which bending failure occurred was recorded.

[0075] (Bending failure state) The bending fracture state was observed when the specimen was bent to fracture.

[0076] (Glue dripping) The state of glue dripping was visually observed. Those that had no glue drips were marked as "○" and passed the test. Anything other than the above was marked as "X" and was deemed a failure.

[0077] (Workability / processability) Generally, the size of decorative boards is 4 shaku x 8 shaku, or about 1200 mm x 2400 mm. Since this size may be handled manually, it is necessary to consider the hardness and weight of the decorative board and confirm the workability. In addition, from the above perspective, each of the following evaluation methods was individually evaluated for its practicality. Both workability and processability were evaluated separately.

[0078] The evaluation was done on a two-level scale: "○" and "×". Those which were excellent in both workability and processability were rated as "◯" and passed the test. Other than the above, that is, either one or both of the workability and the processability were poor, were marked with "X" and were rejected.

[0079] (Lightweight) Light weight was evaluated. The evaluation was done on a two-level scale: "○" and "×". Those excellent in lightness were rated as "○" and passed the test. Anything other than the above, that is, anything inferior in lightness, was marked as "X" and rejected.

[0080] (Thermal insulation) The heat insulation properties were evaluated. The evaluation was done on a two-level scale: "○" and "×". Those having excellent heat insulation were rated as "○" and passed the test. Other than the above, that is, those having poor heat insulation properties, were marked with "X" and rejected.

[0081] (rigidity) The stiffness was evaluated. The evaluation was done on a two-level scale: "○" and "×". Those having excellent rigidity were rated as "○" and passed the test. Anything other than the above, that is, anything inferior in rigidity, was marked as "X" and rejected.

[0082] (Prepreg performance and productivity) The performance and productivity of the prepreg was evaluated throughout the work. The evaluation was done on a two-level scale: "○" and "×". Those with excellent productivity were rated as "○" and passed the test. Anything other than the above, that is, anything having poor productivity, was marked as "X" and rejected.

[0083] (Observation of condition after bending test) The condition after the bending test was observed, that is, the condition of the "surface layer" and the "foam" was visually observed and evaluated. The evaluation was done on a three-point scale: "○", "△", or "×". Regarding the condition observation after the bending test, if "cracks were only on the surface" after the bending test, it was marked as "○" and it was judged as passing, and if "cracks on the surface" occurred, it was marked as "△" and it was judged as passing. In cases where other than the above, for example, "cracks in the foam" or "peeling off of the foam" occurred, the sample was marked with "X" and was deemed to have failed.

[0084] The condition observation after the bending test was evaluated on a three-point scale, but this is not limited to this. If the evaluation were done on a two-point scale of "○" and "×", it would also be possible to mark the specimen as "×" and judge it as failing if "surface cracks" occurred in addition to "cracks only on the surface".

[0085] (Design) The state of glue dripping was visually inspected and evaluated as design. The evaluation was done on a two-level scale: "○" or "×". Those that had no glue drips were marked as "○" and passed the test. Anything other than the above was marked as "X" and was deemed a failure.

[0086] (Processability (wear of cutting tools)) The workability was evaluated by visually observing the wear of the cutting tool. The evaluation was done on a two-level scale: "○" and "×". The cutting tool that showed no wear was rated as "◯" and passed the test. Anything other than the above was marked as "X" and was deemed a failure.

[0087] (Adhesiveness) The adhesiveness was evaluated based on the state at the time of breakage in a bending breaking strength test. The evaluation was done on a two-level scale: "○" and "×". Those in which the surface layer material and the foam did not peel off when broken were rated as "◯" and passed the test. Those that peeled off were marked as "X" and rejected.

[0088] (comprehensive evaluation) The overall evaluation was made by comprehensively evaluating (3) the state of glue dripping to (12) the state of adhesiveness. The evaluation was done on a two-level scale: "○" and "×". Those which all passed were marked with "○" and deemed to have passed. Anything other than the above was marked as "X" and was deemed a failure.

[0089] In the overall evaluation, all items that passed were marked with an "O" and deemed to have passed, but this is not limited to this. Only items that are all "O" may be marked with an "O" and deemed to have passed, and items other than those, i.e. items that include "△" or "X", may be marked with an "X" and deemed to have failed.

[0090] (Evaluation result 1) The evaluation results 1 of Examples 1 to 11 are as shown in Table 3 below. [Table 3]

[0091] (Evaluation result 2) The evaluation results 2 of Comparative Examples 1 to 8 are as shown in Table 4 below. [Table 4]

[0092] (Evaluation Results of Examples 1 to 11 and Comparative Examples 1 to 8) Comparing the evaluation results of Examples 1 to 11 and Comparative Examples 1 to 8, as shown in Tables 3 and 1, only Examples 1 to 11 were given an overall evaluation of "◯" and passed. In contrast, the overall evaluation of Comparative Examples 1 to 8 was all "x", and all of them failed.

[0093] (Bending strength, bending failure condition, glue duct condition) The bending strength, bending breaking state, and glue duct state are compared between Examples 1 to 11 and Comparative Examples 1 to 8 using Tables 3 and 4, and the results are as follows.

[0094] (Evaluation Results of Example 1) In Example 1, the bending strength of the obtained lightweight board was measured, and it was found that although it was deflected when a load of up to 2.7 kN was applied, it returned to its original state when the load was removed. In contrast, in Example 1, when a load of up to 2.8 kN was applied, only the surface layer cracked, but the foam did not crack.

[0095] Furthermore, in Example 1, when the obtained lightweight board was cut with an electric circular saw, the plastic foam did not melt due to heat, and it could be cut as easily as ordinary wood. Furthermore, the state of glue ducts in Example 1 was passable, with no glue ducts. In addition to Example 1, the remaining Examples 2 to 10 also passed the same test.

[0096] (Evaluation Results of Example 2) In Example 2, the bending strength of the obtained lightweight board was measured, and it was found that although it was deflected when a load of up to 5.9 kN was applied, it returned to its original state when the load was removed. In addition, in Example 2, when a load of up to 6 kN was applied, only the surface layer cracked, but like Example 1, the foam did not crack.

[0097] Furthermore, in Example 2, the obtained lightweight board was cut with an electric circular saw. As in Example 1, the plastic foam did not melt due to heat, and the board could be cut as easily as ordinary wood.

[0098] (Evaluation Results of Example 3) In Example 3, the bending strength of the obtained lightweight board was measured, and it was found that although it was deflected when a load of up to 12.9 kN was applied, it returned to its original state when the load was removed. In addition, in Example 3, when a load of up to 13 kN was applied, only the surface layer cracked, but like Example 1, the foam did not crack. Furthermore, in Example 3, the obtained lightweight board was cut with an electric circular saw. As in Example 1, the plastic foam did not melt due to heat, and the board could be cut as easily as ordinary wood.

[0099] (Evaluation Results of Example 4) In Example 4, the bending strength of the obtained lightweight board was measured, and it was found that although it was deflected when a load of up to 2.4 kN was applied, it returned to its original state when the load was removed. In addition, in Example 4, when a load of up to 2.5 kN was applied, only the surface layer cracked, but like Example 1, the foam did not crack.

[0100] Furthermore, in Example 4, the obtained lightweight board was cut with an electric circular saw. As in Example 1, the plastic foam did not melt due to heat, and the board could be cut as easily as ordinary wood.

[0101] (Evaluation Results of Examples 5 to 10) As shown in Table 3, Examples 5 to 7 had different bending strength values, but the bending failure state was similar to that of Example 1.

[0102] (Evaluation Results of Example 11) In Example 11, the bending strength of the obtained lightweight board was measured, and when a load of up to 2 kN was applied, breakage and cracks occurred only in the surface layer. This is presumably due to the use of a "urea resin" as the thermosetting resin other than one type of resin, such as an epoxy resin, a phenolic resin, an unsaturated polyester resin, or a diallylphthalate resin, or a mixture of two or more types of resins. For this reason, it can be assumed that the use of a thermosetting resin other than "urea resin" is effective in preventing "cracks."

[0103] (Evaluation Results of Comparative Example 1) In Comparative Example 1, as shown in Table 4, when the bending strength of the obtained lightweight board was measured, the surface layer material and the foam broke simultaneously when a load of up to 2 kN was applied.

[0104] (Evaluation Results of Comparative Example 2) In Comparative Example 2, the bending strength of the obtained lightweight board was measured, and it was found that when a load of up to 1 kN was applied, the surface layer material peeled off.

[0105] (About workability and processability) Generally, the size of decorative boards is 4 shaku x 8 shaku, or about 1200mm x 2400mm. Since this size may be handled manually, it is necessary to consider the hardness and weight of the decorative board and check the workability. After manufacturing at this size, cutting will be performed depending on the purpose, so it is desirable to use a general-purpose cutting machine for this, and in this case, a cutting machine for woodworking.

[0106] From the above viewpoints, workability and processability were evaluated. As for the workability and processability, the workability and processability of both Comparative Example 3 and Comparative Example 4 were rated as "x" and were unsatisfactory.

[0107] In Comparative Example 3, the thickness of the surface layer material 12 was 0.15 mm, which was too thin and caused bending, so that it could not be carried unless two sides were supported, and it was poor in workability, so it was rejected. Comparative Example 4 was rejected because the surface layer material 12 had a thickness of 2.4 mm, which was too thick and heavy, and was poor in workability.

[0108] Comparing Examples 1 and 4 with Comparative Examples 3 and 4, it can be inferred that the lower limit of the thickness of the surface layer material 12 exceeds 0.15 mm, and is preferably 0.2 mm or more. It can be inferred that the upper limit of the thickness of the surface layer material 12 is below 2.4 mm, and is at least 1.6 mm or less, and is preferably 2.0 mm or less.

[0109] (Lightweight, heat insulating, and rigidity) As for the light weight, heat insulation, and rigidity, as shown in Table 4, at least one of the light weight, heat insulation, and rigidity of Comparative Example 5 and Comparative Example 6 was marked "x" and failed. Comparative Example 5 had a four-fold expansion ratio, was inferior in lightness and heat insulation, and was therefore rejected. Comparative Example 6 had an expansion ratio of 23 times, was inferior in rigidity, and was rejected. Comparing Examples 6 and 7 with Comparative Examples 5 and 6, it can be inferred that an expansion ratio of 5 to 20 times is preferable.

[0110] (Prepreg performance and productivity) As for the performance and productivity of the prepregs, as shown in Table 4, the performance and productivity of the prepregs of Comparative Example 7 and Comparative Example 8 were both rated "x" and were unsatisfactory. In Comparative Example 7, the basis weight of the glass cloth is 40 g / m 2 The amount of the impregnated resin was too small to adequately hold the thermosetting impregnating resin, and when the laminate was hot-pressed after impregnation, delamination occurred, so the sample was rejected.

[0111] In Comparative Example 8, the basis weight of the glass cloth is 210 g / m 2 The amount of thermoplastic resin impregnated was too much, drying could not be performed sufficiently, and blocking (sticking) occurred between the prepregs, so it was rejected. Comparing Examples 1 and 5 with Comparative Examples 7 and 8, the basis weight of the glass cloth is 50 g / m 2 More than 200g / m 2 The following ranges can be assumed to be good:

[0112] (Observation of condition after bending test) Regarding the observation of the state after the bending test, as shown in Table 4, the state observation after the bending test of Comparative Example 1 and Comparative Example 2 was all marked "x", indicating failure. In Comparative Example 1, polystyrene was used as the foam material, and when a load of up to 2 kN was applied, the surface layer material and the foam broke simultaneously, so that the test was rejected.

[0113] In Comparative Example 2, a chloroprene rubber-based adhesive was used, and when a load of up to 1 kN was applied, peeling of the surface layer occurred, and therefore the sample was rejected. Comparing Example 1 with Comparative Examples 1 and 2, it can be inferred that unsaturated polyester resin is preferable as the thermosetting resin, polycarbonate resin is preferable as the foam material, and urethane-based adhesive is preferable.

[0114] (Design) Regarding the design, as shown in Table 4, the design of Comparative Example 3 was rated "X" and was unsatisfactory. In Comparative Example 3, the prepreg was thin at 0.15 mm, and therefore the unevenness of the adhesive application could not be covered up, resulting in a so-called glue-filled area, and the design was poor. Since no glue-filled area occurred with the prepreg having a thickness of 0.2 mm in Example 5, it can be inferred that the prepreg thickness must be 0.2 mm or more.

[0115] (Processability (wear of cutting tools)) Regarding the machinability, as shown in Table 4, the machinability (wear of the cutting tool) of Comparative Example 4 was rated "x", which was unacceptable. Comparative Example 4 was rejected because the thickness of the surface layer material 12 was 2.4 mm, which was too thick and caused wear of the cutting tool. Comparing Example 5 with Comparative Example 4, it can be inferred that the thickness of the surface layer material 12 is preferably 2.0 mm or less.

[0116] (Adhesiveness) Regarding adhesion, as shown in Table 4, the adhesive of Comparative Example 2 was rated as "X" and failed. Since the solid content of the adhesive in Comparative Example 2 was 12%, adhesive containing volatile matter would cause poor adhesion, and therefore the adhesive was deemed to have failed.

[0117] (Embossed) The outermost layer of the lightweight board 10 may be embossed as in the eighth embodiment. The outermost surface layer of the lightweight board 10 can be embossed to provide anti-slip properties. Although the outermost layer of the lightweight board 10 is embossed, the present invention is not limited to this, and the outermost layer of the structural material 20 may be embossed.

[0118] (Additional adhesive information) The adhesive must be 100% solids. This is because adhesives containing volatile components cause poor adhesion. In other words, the volatile components do not soak into the substrate. Therefore, they cannot volatilize, and foaming occurs between the prepreg and the foam 11. [Explanation of symbols]

[0119] 10. Lightweight Board 11 Foam 12 Surface material 20 Structural materials

Claims

1. A surface layer material having a thickness of 0.2 mm to 2.0 mm, which is obtained by impregnating a glass cloth with a thermosetting resin and hot-press molding, is attached to the front and back of a plastic foam having an expansion ratio of 5 to 20 times using an adhesive with a solid content of 100%. The plastic foam is a polycarbonate-based resin, A lightweight board, characterized in that the adhesive having a solid content of 100% is a urethane-based resin (excluding hot melt adhesives) or an epoxy-based resin (excluding hot melt adhesives).

2. The glass cloth has a basis weight of 50 g / m 2 More than 200g / m 2 2. The lightweight board according to claim 1, characterized in that it is in the range of:

3. 3. The lightweight board according to claim 1, wherein the thermosetting resin is one of epoxy resin, phenol resin, polyester resin, and diallylphthalate resin, or a mixture of two or more of these resins.

4. The lightweight board according to any one of claims 1 to 3, characterized in that the number of layers of the glass cloth is two or more.

5. The lightweight board according to claim 1, characterized in that a laminate of the glass cloth and printed paper impregnated with the thermosetting resin is subjected to hot press molding, and multiple decorative panels are bonded to each other using an adhesive having a solid content of 100%, thereby forming the surface material.

6. A surface layer material having a thickness of 0.2 mm to 2.0 mm, which is obtained by impregnating a glass cloth with a thermosetting resin and hot-press molding, is attached to the front and back of a plastic foam having an expansion ratio of 5 to 20 times using an adhesive with a solid content of 100%. The plastic foam is a polycarbonate-based resin, A lightweight board characterized in that a laminate of the glass cloth and printed paper impregnated with the thermosetting resin is subjected to hot press molding, and multiple decorative panels are bonded to each other using the adhesive having a solid content of 100%, thereby forming the surface material.

7. A plastic foam is prepared by foaming a polycarbonate resin at a foaming ratio of 5 to 20 times. A surface layer material having a thickness of 0.2 mm to 2.0 mm is formed by impregnating a glass cloth with a thermosetting resin and hot-press molding the glass cloth, An adhesive having a solid content of 100% is applied to one of the front and back surfaces of the plastic foam body, and the surface layer material is bonded to the adhesive. The adhesive is applied to the other surface of the plastic foam, the surface material is attached, and the surface is dried for a predetermined period of time under pressure. A method for manufacturing a lightweight board, wherein the adhesive having a solid content of 100% is a urethane-based resin (excluding hot melt adhesives) or an epoxy-based resin (excluding hot melt adhesives).

8. 2. A structural material, comprising: the lightweight board according to claim 1 cut into a desired shape; and the cut lightweight boards are joined together with the adhesive to form a desired shape.

9. A plastic foam is prepared by foaming a polycarbonate resin at a foaming ratio of 5 to 20 times. A surface layer material having a thickness of 0.2 mm to 2.0 mm is formed by impregnating a glass cloth with a thermosetting resin and hot-press molding the glass cloth, An adhesive having a solid content of 100% is applied to one of the front and back surfaces of the plastic foam body, and the surface layer material is bonded to the adhesive. A structural material characterized in that the adhesive is applied to the other side of the front or back of the plastic foam, the surface material and the plastic foam are alternately bonded to create a structure, the adhesive is applied to one side of one of both end faces of the structure, the surface material is bonded, and the surface material is bonded to the other side of both end faces of the structure, and four sides are surrounded by the surface material.

Citation Information

Patent Citations

  • High-strength thermoplastic light composite board and preparation method thereof

    CN109177352A

  • Fiber reinforced phenolic resin foam and manufacture thereof

    JP1992062044A

  • Base material for forming interior material for automobile

    JP1996072628A

  • Polycarbonate foam for lamination of fiber-reinforced synthetic resin, composite of said foam and fiber-reinforced synthetic resin, and preparation of said composite

    JP1998130413A

  • Outer panel reinforcing material and method for reinforcing outer panel

    JP2011148091A